2018
DOI: 10.1016/j.fuel.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Controlled delivery and release of surfactant for enhanced oil recovery by nanodroplets

Abstract: Chemical-based oil recovery method has promising applications but suffers the problem of large quantity of chemical loss inside the reservoir. This work proposes an innovative concept of using nanodroplets as carriers for surfactants/polymers and control their release inside porous media to increase oil recovery in water-wet reservoirs. Comparing to conventional surfactant flooding, the proposed concept could not only reduce the adsorption of surfactant on rock surface, but also ease the problem of unstable su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…HPLC system was connected to Evaporative Light Scattering Detector (ELSD) which is a universal detector that is used for the majority of surfactants [77] , [78] . The Thermo Scientific acclaim surfactant plus column (Dionex bonded silica (3 μ, 3.0 × 150nm)) was used for the analysis in this study with high sensitivity and high productivity [79] , [80] . An example of the corresponding peaks of APG and AEC in the obtained chromatogram from HPLC are demonstrated in the supplementary materials (Appendix I).…”
Section: Methodsmentioning
confidence: 99%
“…HPLC system was connected to Evaporative Light Scattering Detector (ELSD) which is a universal detector that is used for the majority of surfactants [77] , [78] . The Thermo Scientific acclaim surfactant plus column (Dionex bonded silica (3 μ, 3.0 × 150nm)) was used for the analysis in this study with high sensitivity and high productivity [79] , [80] . An example of the corresponding peaks of APG and AEC in the obtained chromatogram from HPLC are demonstrated in the supplementary materials (Appendix I).…”
Section: Methodsmentioning
confidence: 99%
“…Further experimental studies will also provide important benchmarks for approximate theoretical methods, as the combination of low temperature, finite-doping, and dynamics is challenging for exact theoretical approaches. [39][40][41][42].…”
mentioning
confidence: 99%
“…Sulfonate groups are present in many known surfactants such as sodium dodecylbenzene sulfonate (SDBS) which have been applied to enhanced oil recovery [11,12,13]. Besides, some other studies [31,39,40,41] showed that these groups have an influence on the polymerization reaction and the obtained particle sizes.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome this disadvantage, systems have been developed in order to stabilize surfactant molecules [5,6,7,8,9,10,11,12,13,14,15,16,17]. For example, Pei et al showed that O/W emulsion injection containing nanoparticles and surfactant can increase the tertiary oil recovery [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation